Beyond GDP - Heun, Matthew Kuperus (Springer, 2015)
This book uses the metaphor “The economy is society's metabolism” as a springboard to develop a rigorous theoretical framework for a better system of national accounts which goes “Beyond GDP” and is relevant to the age of resource depletion. Society is entering a new era in which biophysical limits related to natural resource extraction rates and the biosphere's waste assimilation capacity are becoming binding constraints on mature economies. Unfortunately, the data needed for policy-makers to understand and manage economic growth in this new era are not universally available. All stakeholders need a new way to understand our economy in the context of the biosphere’s ability to provide essential natural capital, and we suggest that detailed information about materials, energy, embodied energy, and energy intensity should be routinely gathered, analyzed, and disseminated from a centralized location to provide markets and policymakers with a more comprehensive understanding of the biophysical economy. However, a firm theoretical foundation is needed before proceeding along this new path, which this book is intended to provide.